Public Relations and Digital Media - Novrian Novrian; Suroso Suroso; Mohamad Sudi; Muhsin Efendi; Geofakta Razali (Lembaga Pengembangan Kinerja Dosen, 2023)
The objective of this essay is As a brand-new form of digital journalism, immersive journalism will be discussed in this article. The media industry uses the hierarchy of influence theory to better understand the context of in-depth journalism. An overview of the state of digital journalism globally and in Indonesia is given in this article. The idea of immersive journalism employs the literary analysis method. The analysis's findings show that the organization's internal and external communications have an impact on the processes of information production, distribution, and consumption. The space for audience engagement that emerges in digital media has the potential to continue for a very long period in immersive journalism, where audiences may actively participate and direct story development. Establishing immersive journalism has been hampered by a number of issues, including the possibility of financial gain, tool adaptation, story development, susceptibility, and manipulation. Media industry players will be compelled to rethink the parameters of engagement, narrative framework, objectivity, and sensitive information with the public if they adopt an in-depth journalistic approach.